Rancang Bangun Sistem Pembaruan Firmware Over-the-Air (OTA) untuk Perangkat ESP32 Berbasis Layanan Cloud - Faris Munir; Basuki Rahmat; Fawwaz Ali Akbar (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The rapid development of Internet of Things (IoT) technology has driven the need for efficient, secure, and reliable firmware update systems. Firmware plays a vital role in maintaining the performance, security, and functionality of IoT devices, including those based on the ESP32, which is widely used due to its cost-effectiveness and connectivity capabilities. However, conventional firmware update methods that require physical connections are inefficient for managing large-scale, distributed devices. Over-the-Air (OTA) technology offers a more relevant solution by enabling wireless firmware updates without manual intervention. This study aims to design and implement a cloud-based OTA firmware update system for ESP32 devices. In this approach, the ESP32 acts as a client that automatically downloads the latest firmware from a cloud server, eliminating the need for a local server infrastructure. The expected outcome is a system capable of efficiently distributing firmware, ensuring the integrity and authenticity of update files, and supporting large-scale IoT device management in a more practical and sustainable manner.